The Distribution of Microplastics in Beach Sand in Tien Giang Province and Vung Tau City, Vietnam - To Thi Hien; Nguyen Thi Thanh Nhon; Vo Thi Minh Thu; Do Thi Thuy Quyen; Nguyen Thao Nguyen (Journal of Engineering and Technological Sciences, 2020)
Microplastics threaten the ecosystem because of undesirable properties such as non-biodegradability, easy-to-absorb persistant organic compounds, etc. They are found worldwide in marine, fresh water and beach sand environments. In this study, microplastics in beach sand samples from two sites in Tien Giang province and two sites in Vung Tau city were investigated. The results showed that the microplastics amount was 0 to 295 pieces/kg dry sand and they mainly distributed near estuarine areas. Microplastics were more prevalent at bathing sites than non-bathing sites. In Tien Giang fragments were the most dominant among the three types of shapes (fragments, fibers, granules) at 60.2%. In Vung Tau granules were most prevalent at 71.7%. The composition of the plastics was confirmed by Fourier-transform infrared spectroscopy. It was revealed that PE, PP and PS were the main types of plastics found in the sampling sites.